Blood pressure, heart rate, and skin temperature in preterm infants: associations with periventricular haemorrhage. Issue 3 (May 1995) - D'Souza, S. W.; Janakova, H.; Minors, D.; Suri, R.; Waterhouse, J.; Appleton, G.; Ramesh, C.; Sims, D. G.; Chiswick, M. L.
Abstract : The mean arterial blood pressure (MABP), heart rate, and skin temperature were monitored every 15 minutes in the first 10 days after birth in 34 preterm infants, gestational age 24 to 33 weeks. Ultrasound brain scans carried out daily showed that a periventricular haemorrhage (PVH) occurred in a subgroup of infants (n = 15) of lower birthweight and gestational age. In infants without PVH the daily median of MABP increased with birthweight and postnatal age; that of heart rate was not affected by postnatal age, body weight, or gestational age; and that of skin temperature showed a slight fall with postnatal age. In infants with PVH, on or before the day of PVH, daily medians of MABP and skin temperature were not significantly different from those of infants without PVH, but the daily median of heart rate tended to be slightly higher. The percentage of positive correlations between the 96 15 minute values per day for heart rate and MABP increased with postnatal age and with birthweight, but did not differ in infants who developed a PVH. The coefficient of variation (CV) of the 96 15 minute values for MABP tended to be higher in infants on the day of PVH, and a similar trend was apparent on the day before. The processes of development of blood pressure, heart rate, and skin temperature are similar in infants with or without PVH but at lower gestational ages altered blood pressure control may cause brain haemorrhage.